Perception of Stand-on-ability: Do Geographical Slants Feel Steeper Than They Look?. (July 2016) - Hajnal, Alen; Wagman, Jeffrey B.; Doyon, Jonathan K.; Clark, Joseph D.
Past research has shown that haptically perceived surface slant by foot is matched with visually perceived slant by a factor of 0.81. Slopes perceived visually appear shallower than when stood on without looking. We sought to identify the sources of this discrepancy by asking participants to judge whether they would be able to stand on an inclined ramp. In the first experiment, visual perception was compared to pedal perception in which participants took half a step with one foot onto an occluded ramp. Visual perception closely matched the actual maximal slope angle that one could stand on, whereas pedal perception underestimated it. Participants may have been less stable in the pedal condition while taking half a step onto the ramp. We controlled for this by having participants hold onto a sturdy tripod in the pedal condition (Experiment 2). This did not eliminate the difference between visual and haptic perception, but repeating the task while sitting on a chair did (Experiment 3). Beyond balance requirements, pedal perception may also be constrained by the limited range of motion at the ankle and knee joints while standing. Indeed, when we restricted range of motion by wearing an ankle brace pedal perception underestimated the affordance (Experiment 4). Implications for ecological theory were offered by discussing the notion of functional equivalence and the role of exploration in perception.